Serum IL-15 and IL-21 as Diagnostic and Severity Biomarkers in Treatment-Naïve Celiac Disease: A Case-Control Study - Dr. Israa Abdulwahid Dheeb, (American Journal of Biology and Natural Sciences, 2026)
Celiac disease (CD) is an enteropathy characterized by chronic immune-mediated intestinal damage due to dietary gluten. The consequence of celiac disease is a gradual decline of the small intestinal mucosal layer, dysregulated cytokine signaling, and a deranged balance between the two branches of the immune system (innate and adaptive). The pro-inflammatory cytokines IL-15 and IL-21 are involved as mediators for both innate and adaptive immunity in the development of celiac disease; however, very limited research has been conducted on the levels of IL-15 and IL-21 in patients with celiac disease prior to treatment (i.e., "treatment-naive") due to insufficient data that indicates their diagnostic usefulness and ability to reflect the severity of the disease in the population living in the Arab states of the Middle East (ME). In view of this gap in the existing literature, we aim to evaluate the concentrations of IL-15 and IL-21 in serum of treatment-naive patients with celiac disease to establish their utility as non-invasive markers for diagnosing celiac disease and assessing disease severity. Design: This was a prospective case-control study of 40 celiac disease patients who had never been treated and 40 matched healthy controls from the being seen in the Gastroenterology Unit at Al Diwaniyah Teaching Hospital, Iraq between October 2025 - April 2026. Serum concentrations of IL-15 and IL-21 were determined by using a sandwich enzyme-linked immunosorbent assay (sandwich ELISA). The Marsh-Oberhuber histopathological classification was used to evaluate disease severity. Receiver Operating Characteristic (ROC) curve analysis was then used to evaluate diagnostic accuracy. Pearson’s Correlation Analysis was used examine the relationship between cytokine concentrations and disease severity criteria. The results of our study indicate that there were significantly higher levels of serum IL-15 in patients with celiac disease as compared to healthy control subjects (148.6 ± 28.4 pg/mL vs. 42.3 ± 11.7 pg/mL; P = 0.001). Thus, patients had approximately 3.5 times the level of IL-15 than did the healthy controls. In addition, IL21 serum levels were found to be significantly higher among celiac disease patients than among healthy control subjects (312.4 ± 54.7 pg/mL vs. 87.6 ± 21.3 pg/ mL; P < 0.001), with approximately 3.6 times the level of serum IL-21 in celiac patients compared to healthy controls. The results of receiver operating characteristic (ROC) curve analysis also showed high sensitivity and specificity for both IL-15 (> 85.5pg/ml cutoff; 92.5% and 95%, respectively) and IL-21 (> 178.3 pg/ml cutoff; 95% and 97.5%, respectively). The area under the ROC curves (AUC) were il15 [AUC 0.981 (95%CI 0.956-1.000)] and il21 [AUC 0.994 (95%CI 0.985-1.000)] therefore indicating that these two measures would be useful as diagnostic tools for the diagnosis of celiac disease. IL-15 and il-21 serum levels were positively related to Marsh/Oberhuber histological staging (r = 0.782, P < 0.001 and r = 0.841, P < 0.001) as well as IL-15 being positively related to IL-21 (r = 0.614; P < 0.001). Concluding Remarks: Elevated serum levels of interleukin-15 and interleukin-21 from untreated patients with celiac disease demonstrate systemic elevation of both the innate and adaptive pro-inflammatory immune pathways. The diagnostic accuracy of both cytokines exceeded 0.98 AUC, suggesting they may serve as non-invasive biomarkers for the diagnosis of celiac disease, while also demonstrating correlation with the severity of histopathological mucosal damage based upon the Marsh-Oberhuber grading system. Therefore, the serum levels of interleukin-15 and interleukin-21 represent promising non-invasive biomarkers for diagnosis and classification of the severity of celiac disease, with potential for use as monitoring or assessment of clinical response to therapy.